Correlation of anthropometric indices with rate pressure product in healthy young adults - Sunil Kumar Jena; Kanhu Charan Purohit; Biswabhusan Mohanty (Wolters Kluwer Medknow Publications, 2017)
Background: Generalized and abdominal obesity is associated with increased incidence of adverse cardiovascular events. Rate pressure product (RPP) is an indicator of myocardial oxygen consumption, and higher value of RPP indicates myocardial work stress or cardiovascular risk. Thus, RPP can be correlated with anthropometric indices such as body mass index (BMI), waist circumference (WC), and waist-hip ratio (WHR) to evaluate the risk of adiposity on myocardial work stress. Materials and Methods: In this study, 104 young male college students were recruited as subjects. Height, weight, WC, and hip circumference were measured whereas BMI and WHR were derived by specific formula. Heart rate (HR) and blood pressure (BP) were recorded after allowing for 10 min rest and RPP was derived by specific formula. Subjects were distributed into different groups considering BMI, WC, and WHR. The analysis of parameters, i.e., systolic BP, HR, and RPP was done by one-way ANOVA, unpaired t-test, and Pearson correlation. Results: The major findings of this study suggested that obese and overweight subject RPP was more than normal participants. The subjects of WC >90 cm had higher RPP than the subjects of WC ≤90 cm. The subjects of WHR ≥0.90 had higher RPP than WHR <0.90. There was a significant positive correlation (P < 0.05) between RPP and anthropometric indices, i.e., BMI, WC, and WHR. Conclusion: Vital parameters of adiposity or obesity such as BMI, WC, and WHR may be used to evaluate the risk of myocardial work stress or cardiovascular events in correlation with RPP.